+0  
 
0
283
2
avatar

how do i factor out 6x^2-x-1?

Guest Oct 29, 2015

Best Answer 

 #1
avatar+1792 
+10

Since the constant term is -1 you know your factors are going to be

 

\(6x^2 -x -1 = (a x + 1)(b x -1) = (ab)x^2+(b-a)x-1\)

 

\(a b =6, (b-a)=-1 \\ b=a-1 \\ a(a-1) = 6 \\ a=3, b=2\)

 

\(6x^2-x-1 = (3x+1)(2x-1)\)

Rom  Oct 29, 2015
Sort: 

2+0 Answers

 #1
avatar+1792 
+10
Best Answer

Since the constant term is -1 you know your factors are going to be

 

\(6x^2 -x -1 = (a x + 1)(b x -1) = (ab)x^2+(b-a)x-1\)

 

\(a b =6, (b-a)=-1 \\ b=a-1 \\ a(a-1) = 6 \\ a=3, b=2\)

 

\(6x^2-x-1 = (3x+1)(2x-1)\)

Rom  Oct 29, 2015
 #2
avatar+91053 
0

 

Thansk Rom    smiley

I would not have done it like that but I like that logic.

To use Chris's expression,  "I will put that in my tool belt"

I think that is what chris says anyway LOL

Melody  Oct 29, 2015

3 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details